(untitled) (Edad Media. Revista de Historia, 2025)
An erroneous binding has greatly hindered the understanding of the Becerro Gótico of Valvanera. In this paper, analysing the volume’s internal logic, we reconstruct its original order. What emerges is one of the earliest cartularies composed in Iberia. Unlike memorial cartularies, this is an administrative cartulary, added to diachronically, but over a strikingly brief period of time. It was essentially conceived as a project around 1078, and was largely completed by 1082. It would later see the incorporation of some additions in available spaces, before what is today its opening quire was added towards the beginning of the 12th century, with the cartulary acquiring its definitive form around 1110.